Growth Performance, Antioxidants, Intestinal Microbial Composition and Histological Effect of Grass Carp (Ctenopharyngodon idella) through diets Enriched to Pomegranate Peel (Punica granatum) Extracts - Hassan. A. Fazaa; Fatima A.M. Sultan; Raad M. Sayed-Lafi (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract